2016
DOI: 10.1099/jgv.0.000445
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of microRNA-122 binding sequences of hepatitis C virus and identification of variants with high resistance against a specific antagomir

Abstract: MicroRNA 122 (miR-122) stimulates the replication and translation of hepatitis C virus (HCV) RNA by binding to two adjacent sites, S1 and S2, within the HCV 5¢UTR. We demonstrated previously that the miR-122 antagomir miravirsen (SPC3649) suppresses the infection of HCV strain JFH1-based recombinants with HCV genotypes 1-6 5¢UTR-NS2 in human hepatoma Huh7.5 cells. However, specific S1 mutations were permitted and conferred virus resistance to miravirsen treatment. Here, using the J6 (genotype 2a) 5¢UTR-NS2 JFH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Importantly, the administration of Miravirsen in patients with chronic HCV-1 displayed extended dose-dependent diminutions in HCV RNA levels without any manifestation of viral resistance (Janssen et al, 2013). However, it was found that long term treatment with Miravirsen in vitro induces resistance due to mutations in the viral genome (Ottosen et al, 2015, Li et al, 2016). …”
Section: First Clinical Trials With Mirnasmentioning
confidence: 99%
“…Importantly, the administration of Miravirsen in patients with chronic HCV-1 displayed extended dose-dependent diminutions in HCV RNA levels without any manifestation of viral resistance (Janssen et al, 2013). However, it was found that long term treatment with Miravirsen in vitro induces resistance due to mutations in the viral genome (Ottosen et al, 2015, Li et al, 2016). …”
Section: First Clinical Trials With Mirnasmentioning
confidence: 99%
“…For example, miR122 can modify the viral RNA base pairing and increase its half-life, promoting translation and protection of HCV RNA [138,282]. The emergence of resistant virus strains to miR-122 inhibitors with enhanced genome stability and protection against host RNases has recently been reported [283]. Therefore, the ability of host RNases to target viral RNA might be hindered by the presence of a diversity of ncRNAs.…”
Section: Other Rnasesmentioning
confidence: 99%
“…Traditionally, miRNA binds to the 3 0 untranslated region (3 0 UTR) of the target RNAs (Chen et al 2016;Riess et al 2016;Zuo et al 2016;Zhang et al 2016a;Zhang et al 2016c;Hazra et al 2017;Yu et al 2017;Yang et al 2017b;Trobaugh et al 2019). However, growing evidences have showed that miRNA can also bind to the 5 0 UTR and coding region of target RNAs (Akhtar et al 2015;Li et al 2016;Niederr€ ohrmann et al 2016;Gerresheim et al 2017;Gutkoska et al 2017). miRNA participates in various biological processes of eukaryotes, including cell proliferation, development, differentiation, metabolism, tumorigenesis and apoptosis (Contreras et al 2015;Hajarnis et al 2017;Li et al 2017;Zhao et al 2017;Liu et al 2017a;Gomez et al 2020;Farina et al 2020), Moreover, it also plays an extremely important role in the regulation of viral replication.…”
Section: Introductionmentioning
confidence: 99%